Regional mineral and raw material bases as a key factor in the development of Ukraine during the war and post-war periods - Вижва, С.; Курило, М.; Віршило, І. (Київський національний університет імені Тараса Шевченка, 2023)
In the study, an analysis of the regional components of the mineral and raw material base of Ukraine was carried out, and its structure was determined. Regions were analyzed according to a number of basic characteristics: the intensity of subsoil use, minerals production, the level of geological study, the level of industrial development of explored mineral reserves, and the presence of strategically important minerals. It was determined that the main disadvantage of individual regional components of the mineral raw material base is the uneven distribution of reserves and inferred resources, as well as the asymmetric distribution of consumers of mineral raw materials. The changes in the regional structure of the mineral and raw material base of Ukraine were analyzed and directions for their optimization were determined in order to achieve balanced indicators of development. The results indicate significant differences in the structure of the mineral base of individual regions. The number of mineral deposits varies significantly – from ≈100 to ≈700, exploited deposits – from 35 to ≈300. The average values of these indicators in Ukraine are 348 and 130 objects. The average rate of objects involved in industrial development by region is 37%. Characteristics such as the structure of explored reserves by type of minerals and the size and quality of reserves are determined. In order to provide the regions with construction materials and fuel resources in a timely and continuous manner, an up-to-date reassessment of the regional mineral and raw material bases is necessary, taking into account the damages and violations that occurred as a result of military operations, and with the assessment of modern needs and opportunities of the damaged infrastructure.

Проведено аналіз регіональних складових мінерально-сировинної бази України, визначено її структуру. Проведено аналіз областей і регіонів за рядом базових ознак: інтенсивністю надрокористування, ступенем геологічного вивчення родовищ, ступенем промислового освоєння розвіданих запасів корисних копалин, за наявністю стратегічно важливих корисних копалин. Визначено, що головним недоліком окремих регіональних складових мінерально-сировинної бази є нерівномірний розподіл запасів і прогнозних ресурсів, а також асиметричний розподіл споживачів мінеральної сировини. Наведені результати свідчать про істотні відмінності у структурі мінерально-сировинної бази окремих областей. Кількості родовищ корисних копалин та об'єктів обліку змінюється в значних межах – від ≈100 до ≈700, а родовищ, які експлуатуються, – від 35 до ≈300. Середні значення цих показників по Україні становлять 348 та 130 об'єктів. Середній показник залучених у промислове освоєння об'єктів по областях сягає 37 %. Проаналізовано зміни в регіональній структурі мінерально-сировинної бази України та визначено напрями їхньої оптимізації задля досягнення збалансованих показників освоєння. Для своєчасного і безперервного забезпечення регіонів будівельними матеріалами і паливними ресурсами необхідна актуальна переоцінка регіональних мінерально-сировинних баз із врахуванням збитків і порушень, які виникли в результаті військових дій, і з проведенням оцінки сучасних потреб і можливостей порушеної інфраструктури.
Регіональні мінерально-сировинні бази – ключовий фактор у відбудові України у воєнний і повоєнний періоди
Keywords: мінерально-сировинна база; регіональна структура; ресурси; розподіл; mineral and raw material base; regional structure; resources; distribution